The complete mitochondrial genome of Luehdorfia chinensis Leech (Lepidoptera: Papilionidae) from China. Issue 1 (1st January 2016) - Dong, Yan; Zhu, Li-Xin; Wang, Chang-Bao; Zhang, Min; Ding, Pei-Pei
Abstract: The complete mitochondrial genome of Luehdorfia chinensis that is endemic to China is determined. The circular genome is 15 550 bp in length and comprises 13 protein-coding genes (PCGs), 22 tRNAs, two rRNA gene and a control region. Gene order is identical to that of the putative ancestral arrangement of insects. The nucleotide composition of heavy strand is A (40.3%), C (11.2%), T (41.1%) and G (7.3%). All PCGs start with a typical ATN codon except for the gene COI that uses AAC as the start codon. Bayesian analyses support the monophyly of genus Papilio and the sister relationship of Luehdorfia chinensis and L. taibai .